Understanding the audience in framing research: empirical evidence from three studies examining HIV framing in China - Chen, Tianen; Dai, Minhao; Harrington, Nancy Grant (Frontiers in Public Health, 2023)
Guided by framing theory, this three-phase mixed-methods study explored (a) how Chinese government-sponsored newspapers frame HIV and (b) framing effects on people's HIV beliefs. A content analysis of two government-sponsored newspapers and a survey of 210 readers showed discrepancies in frame and frame valence. In-depth follow-up interviews with 15 media and public health experts revealed that the discrepancies were related to people's attitudes toward the media and beliefs about HIV, which could further be explained by the political environment, media ecology, historical framing, and cultural identities in China. We discuss theoretical implications for framing theory and practical implications for HIV coverage.